MENGUNGKAP TANTANGAN DAN SOLUSI DALAM PENULISAN AKADEMIK: STUDI KASUS MAHASISWA DEPARTEMEN BAHASA INGGRIS TAHUN KE-3 UNIVERSITAS AHMAD DAHLAN - Wahyu Rahmadhani Mardalis; Bambang Widi Pratolo (Madah: Jurnal Bahasa dan Sastra, 2024)
Despite living in an era of increasingly advanced digital technology, students still face significant challenges in academic writing, particularly in developing knowledge and writing skills of academic papers at a college level. This study aimed to highlightÂ  Â challenges faced by students in academic writing activities and how they solved the problems. The subjects of this research were five 3rd year students of the English Department of Universitas Ahmad Dahlan. The data of this study were collected by using observation, interviews, and focus group discussion (FGD) techniques. NVivo software was employed as the data analysis tool to make it easier for the researchers to determine the theme of the interview results. The findings show that the most challenging aspects of academic writing are the lack of vocabulary and the lack of skills in writing academic papers. The third year students of the English Department of Ahmad Dahlan University faced challenges in academic writing due to their lack of vocabulary and skills, however they use digital technology and artificial intelligence (AI) to overcome this problem.